2015
DOI: 10.1021/acs.nanolett.5b00542
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Probing of Local Electrical Characteristics on MBE-Grown Bi2Te3 Surfaces under Ambient Conditions

Abstract: The local electrical characteristics on the surface of MBE-grown Bi2Te3 are probed under ambient conditions by conductive atomic force microscopy. Nanoscale mapping reveals a 10-100× enhancement in current at step-edges compared to that on terraces. Analysis of the local current-voltage characteristics indicates that the transport mechanism is similar for step-edges and terraces. Comparison of the results with those for control samples shows that the current enhancement is not a measurement artifact but instea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 40 publications
4
27
0
Order By: Relevance
“…Fig. 2 confirmed that the structure of these synthesised samples had in nano scales in crystalline form according to other researcher reports [17, 18]. The roughness parameter was also observed through these samples.…”
Section: Resultssupporting
confidence: 88%
“…Fig. 2 confirmed that the structure of these synthesised samples had in nano scales in crystalline form according to other researcher reports [17, 18]. The roughness parameter was also observed through these samples.…”
Section: Resultssupporting
confidence: 88%
“…Bi 2 Se 3 thin film was produced by MBE system vaporized onto substrates (mica) . MoO 3 thin film was fabricated on the Bi 2 Se 3 using ZD‐400 (thermal deposition equipment).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we may conclude that CO 2 plays no role in the surface degradation. [23][24][25][26][27] . By analogy with Sb 2 Te 3 the scattering and differences between the published experimental data can be attributed to the fact that the induction period is huge due to the low probability of the elementary chemical reaction event, which occurs on a time scale comparable with or faster than the time scale of experimental exposures.…”
Section: Introductionmentioning
confidence: 99%